Inflammatory demyelinating polyneuropathy in a haemophiliac associated with human immunodeficiency virus infection, responding to high dose intravenous immunoglobulin. Issue 755 (September 1988) - Panicker, R.; Bloom, A. L.; Compston, D. A.
Abstract : We describe what we believe to be the first case of chronic inflammatory demyelinating polyneuropathy (CIDP) occurring in a haemophiliac infected with the human immunodeficiency virus (HIV), and the first patient to show a clinical response to treatment with high dose i.v. immunoglobulin. A 55 year old, severe haemophiliac, known to be positive for HIV antibody, presented with a short history of motor weakness and variable sensory loss in both lower limbs. Clinical examination, electrophysiology and sural nerve biopsy confirmed a diagnosis of CIDP. He was treated with a 4-day course of high dose i.v. immunoglobulin, given as a daily infusion. This resulted in dramatic improvement in his neurological status which was evident both clinically and functionally. We conclude that CIDP can occur in HIV-positive haemophiliacs as it does in homosexuals and drug abusers infected with the virus. We also suggest that high dose i.v. immunoglobulin may be effective in the treatment of this condition, especially when practical difficulties preclude the use of plasmapheresis and the use of immunosuppressive drugs is considered hazardous.